2022
DOI: 10.1002/lary.30255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cough Airflow and Acoustics After Injection Laryngoplasty

Abstract: Objective/Hypothesis We explored the following hypotheses in a cohort of patients undergoing injection laryngoplasty: (1) glottic insufficiency affects voluntary cough airflow dynamics and restoring glottic competence may improve parameters of cough strength, (2) cough strength can be inferred from cough acoustic signal, and (3) glottic competence changes cough sounds and correlates with spectrogram morphology. Study Type/Design Prospective interventional study. Methods Subjects with glottic insufficiency seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Rameau et al pursued a prospective interventional study to explore whether performing IL changed voluntary cough airflow dynamics in outpatients with glottic insufficiency of heterogeneous etiology. 5 They found that IL significantly decreased cough peak expiratory flow rise time and increased cough volume acceleration, suggesting an improvement in cough effectiveness. While targeting glottic competence with IL has long been presumed to improve cough function, this is the first study to quantify this benefit and provides a solid framework for future research.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Rameau et al pursued a prospective interventional study to explore whether performing IL changed voluntary cough airflow dynamics in outpatients with glottic insufficiency of heterogeneous etiology. 5 They found that IL significantly decreased cough peak expiratory flow rise time and increased cough volume acceleration, suggesting an improvement in cough effectiveness. While targeting glottic competence with IL has long been presumed to improve cough function, this is the first study to quantify this benefit and provides a solid framework for future research.…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, swallowing dysfunction lies on a continuum and optimizing cough function to expel aspirated material can still decrease the risk of pneumonia. Rameau et al pursued a prospective interventional study to explore whether performing IL changed voluntary cough airflow dynamics in outpatients with glottic insufficiency of heterogeneous etiology 5 . They found that IL significantly decreased cough peak expiratory flow rise time and increased cough volume acceleration, suggesting an improvement in cough effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Methods for noninvasively assessing swallowing may help detect HNC patients at risk for functional disability. Several teams are investigating cough sounds and voice features as biomarkers of swallowing dysfunction using ML [70,71,72 ▪ ,73 ▪ ]. Others are studying high-resolution cervical auscultation (HRCA), which applies ML and time-series analysis to swallowing-induced acoustic and vibratory signals acquired from neck-attached sensors.…”
Section: Machine Learning Applications To Assess Voice and Swallowing...mentioning
confidence: 99%